2022
DOI: 10.1039/d2na00348a
|View full text |Cite
|
Sign up to set email alerts
|

N-doped graphene for electrocatalytic O2 and CO2 reduction

Abstract: Electrocatalytic CO2 reduction reactions (CO2RR) and oxygen reduction reaction (ORR) are important approaches to realize energy conversion and sustainable development. However, sluggish reaction kinetics severely hinders the practical application of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…Carbonbased catalysts having single-atom metal centres in graphene sheets have been identified as promising candidates for electrochemical ORR and CO 2 RR. 1,2 Numerous studies have revealed that the active site in these catalysts is an MN 4 structure, in which the metal centre is captured by an N 4 structure composed of four pyridine moieties with a 14-membered ring (14MR) around the metal ion. [3][4][5][6] From this perspective, 14MR-MN 4 complexes with H 2 HAM ligand (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonbased catalysts having single-atom metal centres in graphene sheets have been identified as promising candidates for electrochemical ORR and CO 2 RR. 1,2 Numerous studies have revealed that the active site in these catalysts is an MN 4 structure, in which the metal centre is captured by an N 4 structure composed of four pyridine moieties with a 14-membered ring (14MR) around the metal ion. [3][4][5][6] From this perspective, 14MR-MN 4 complexes with H 2 HAM ligand (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Copper-based nanoscale electrocatalysts have shown great potential in the electroreduction of carbon dioxide to multicarbon products; however, their catalytic efficiency is still low. The results show that at least two neighboring copper sites are required to achieve C–C coupling on copper-based electrocatalysts, , while C 1 products are formed on dispersed copper sites. Based on this result, it is expected to improve the selectivity of multicarbon products by precisely controlling the arrangement of copper atoms in copper-based electrocatalysts. For example, Zheng et al effectively shortened the distance between two single copper atoms by increasing the distribution concentration of copper single atoms on the carrier.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] The former generally use commercially available carbons as starting materials, while the latter use nitrogen rich organic compounds as precursors, which allow to tune the nitrogen content in the graphene layers. [21] For instance, the synthesis of N-doped graphene quantum dots via a multi-step procedure, involving the oxidation of commercially available graphite powder, graphene oxide exfoliation and functionalization with dimethylformamide, represents an example of top-down approach. [20] This carbon-based electrocatalyst possessed 6 at % N atoms and produced C 2 (31 % FE) and C 2 oxygenated products (26 % FE) at À 0.75 V vs RHE.…”
Section: Introductionmentioning
confidence: 99%
“…Two main strategies are commonly adopted for the synthesis of N‐doped carbon electrocatalysts: top‐down approaches (hydrothermal, mechanical exfoliation, plasma treatment and arc‐discharge method) and bottom‐up approaches (chemical vapor deposition, solvothermal method and free‐radical polymerization) [20,21] . The former generally use commercially available carbons as starting materials, while the latter use nitrogen rich organic compounds as precursors, which allow to tune the nitrogen content in the graphene layers [21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation